Europe and Central Asia Economic Update, October 2017 : Migration and Mobility - World Bank (Washington, DC, 2017)
Public concerns in Europe and Central Asia over the recent sharp increase in asylum seekers and undocumented migrants seem to reflect a broader anxiety about reduced job security, caused by technological developments and internationalization of production and work. Policy reforms should help both migrants and non-migrants cope with increased and unavoidable flexibility in labor markets.